Pemeriksaan Kesehatan Dan Edukasi Kesehatan Masyarakat Desa Kamal Dalam Upaya Mengontrol Kadar Gula Darah - Aggustin, Ayu Tri; Wijaya, Anas Fadli; Muflihah, Ahdiah Imroatul; Hidayati, Sholihatil (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service activity is a form of effort to support the government program "Healthy Communities that are Independent and Just. The target subjects for partners in this community service activity are the people in Kamal Village, Arjasa District, and Jember Regency. Preliminary studies have been carried out and show that the incidence rate in the village is very high. Thus, health checks and health promotion in an effort to control blood sugar levels through the use of natural germplasm are very necessary. The health checks that will be carried out include random blood sugar checks (GDS). The education provided can include understanding the causes, signs and symptoms, risk factors, and types of healthy nutrition to prevent and control complications of diabetes mellitus. Early screening can be done by carrying out laboratory examinations in the community. After the examination, it was discovered that some people experienced hyperglycemia and some experienced hypoglycemia. Through this activity, the public can understand the material presented and can find out their health status so that early prevention can be carried out.